Total synthesis of insect sex pheromones: recent improvements based on iron-mediated cross-coupling chemistry - Gayon, Eric; Lefèvre, Guillaume; Guerret, Olivier; Tintar, Adrien; Chourreu, Pablo (Beilstein Journal of Organic Chemistry, 2023)
In the current ecological context, use of insect sex pheromones as an alternative to conventional pesticides is in constant growth. In this report, we discuss the recent contributions brought by our groups in the field of iron-catalyzed cross-couplings applied to the synthesis of insect pheromones. The pivotal question of the development of sustainable synthetic procedures involving cheap, non-toxic and efficient additives is also discussed, as well as the mechanistic features guiding the reactivity of such catalytic systems.
Keywords: catalysis; cross-coupling; insect pheromones; iron